1998
DOI: 10.1046/j.1365-2702.1998.00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Important aspects of nursing care in surgical wards as expressed by nurses

Abstract: The aim of this study was to find out clinical nurses' perceptions of important aspects of nursing care that might have an impact on quality of care in surgical wards. A qualitative approach using focus group interviews was used. The data analysis revealed 15 categories of important aspects of care which could be condensed into two dimensions, here called 'prerequisites' (i.e., staffing, routines and attitudes) and 'elements of performance' (i.e., detecting and acting on signs and symptoms and acting on behalf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 20 publications
2
44
0
3
Order By: Relevance
“…Development of this instrument started with a qualitative approach using interviews (Idvall and Rooke, 1998) and a literature review (Idvall et al, 1999) that led to the items tested for content validity (Idvall et al, 2001). Content validity and psychometric properties gave initial support for the instrument with a Cronbach's alpha of 0.84 and inter-item correlation of 0.32 (Idvall et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…Development of this instrument started with a qualitative approach using interviews (Idvall and Rooke, 1998) and a literature review (Idvall et al, 1999) that led to the items tested for content validity (Idvall et al, 2001). Content validity and psychometric properties gave initial support for the instrument with a Cronbach's alpha of 0.84 and inter-item correlation of 0.32 (Idvall et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…Approaches that respect the individuality of patients, such as appropriate communication, caring, informing, and respecting the patients and their autonomy, form the basis of an environment of mutual trust. 9,12,23 This study examined the opinions and practices of patients and their nurses regarding facilitating and maintaining patient privacy in the light of various hospital processes related to hospital stays involving surgery. Most of the nurses and half of the patients in this study wearing the surgical gowns stated that they found the gowns inappropriate; however, it was determined that neither side feel responsible for changing the arrangement in this regard.…”
mentioning
confidence: 99%
“…An instrument to measure the quality of postoperative pain management, Strategic and Clinical Quality Indicators in Postoperative Pain Management, has recently been developed 8 from a qualitative approach using focus group interviews. 9 The items which emerged from the interviews were tested for content validity 10 11 using the method proposed by Fehring. 12 The items were assessed as being (a) essential for the quality of care in postoperative pain management, (b) realistic to carry out, and (c) possible for nurses to influence management.…”
mentioning
confidence: 99%